Issues on visual representation of hybrid home environments: survey of strategies and models. (2015) - Grivas, Konstantinos; Zerefos, Stelios
This survey paper addresses the representation of complex networks in an augmented home environment. The internal and external connections made by wirelessly connected devices, remain unseen, undermining the ability to perceive home in its totality. In order to help reveal the structure, form and perplexity of an augmented home environment, we elaborate on appropriate ways to represent visually those complex relations by making a survey of existing practices and models of complex spatial, territorial and networking visualisations. The survey examines the typologies and functionalities of complex network visualisations, currently available, as a source for basing hybrid home-network maps. It also considers that established mapping and visualisation practices which territorialise information and adjust to cognitive mapping provide equally useful references. Factors like projection, orientation, scale and graphic language have to be adjusted to 'home use/rs'. Finally, the immersive viewpoint is analysed as a complementary visualisation tool for augmented home environments.